Type-I Interferons Inhibit Interleukin-10 Signaling and Favor Type 1 Diabetes Development in Nonobese Diabetic Mice - Iglesias, Marcos; Arun, Anirudh; Chicco, Maria; Lam, Brandon; Talbot, C. Conover; Ivanova, Vera; Lee, W. P. A.; Brandacher, Gerald; Raimondi, Giorgio (Frontiers in Immunology, 2018)
Destruction of insulin-producing -cells by autoreactive T lymphocytes leads to the development of type 1 diabetes. Type I interferons (TI-IFN) and interleukin-10 (IL-10) have been connected with the pathophysiology of this disease; however, their interplay in the modulation of diabetogenic T cells remains unknown. We have discovered that TI-IFN cause a selective inhibition of IL-10 signaling in effector and regulatory T cells, altering their responses. This correlates with diabetes development in NOD mice, where the inhibition is also spatially localized to T cells of pancreatic and mesenteric lymph nodes. IL-10 signaling inhibition is reversible and can be restored via blockade of TI-IFN/IFN-R interaction, paralleling with the resulting delay in diabetes onset and reduced severity. Overall, we propose a novel molecular link between TI-IFN and IL-10 signaling that helps better understand the complex dynamics of autoimmune diabetes development and reveals new strategies of intervention.